Molecular Sieving Film Prepared by Vacuum Filtration for the Efficient Removal of Tetracycline Antibiotics from Pharmaceutical Wastewater. (18th March 2019) - Song, Zhi; Ma, Yu-Long; Li, Cong-Er; Xu, Man; Zhang, Cong
Abstract : The pharmaceutical wastewater (PW) produced during the production of antibiotics has a huge impact on the ecological environment. The efficient removal of residual antibiotics from PW has become a great challenge. Here, a ZIF-8/GO composite film, a new material, was prepared by loading ZIF-8/GO nanosheets onto the surface of a polyethyleneimine- (PEI-) modified nylon microporous support. This new material can effectively remove tetracycline (TC) from PW with a removal rate of 99%. In addition, the layer of ZIF-8/GO nanosheets on the surface of the carrier had certain defect sites. This feature not only made the film have a relatively high flux (502 L·m −2 ·h −1 ·bar −1 ) but also overcame the disadvantages of the traditional membrane separation technology, such as the high operation pressure required by the easy plugging of micropores. More importantly, the abovementioned advantages enable the novel material to be applied on a larger scale. A probable adsorption mechanism was investigated and suggested.